Experimental febrile seizures impair interastrocytic gap junction coupling in juvenile mice. Issue 9 (1st March 2016) - Khan, Dilaware; Dupper, Alexander; Deshpande, Tushar; Graan, Pierre N.E. De; Steinhäuser, Christian; Bedner, Peter
Abstract : Prolonged and focal febrile seizures (FSs) have been associated with the development of temporal lobe epilepsy (TLE), although the underlying mechanism and the contribution of predisposing risk factors are still poorly understood. Using a kainate model of TLE, we previously provided strong evidence that interruption of astrocyte gap junction‐mediated intercellular communication represents a crucial event in epileptogenesis. To elucidate this aspect further, we induced seizures in immature mice by hyperthermia (HT) to study the consequences of FSs on the hippocampal astrocytic network. Changes in interastrocytic coupling were assessed by tracer diffusion studies in acute slices from mice 5 days after experimental FS induction. The results reveal that HT‐induced FSs cause a pronounced reduction of astrocyte gap junctional coupling in the hippocampus by more than 50%. Western blot analysis indicated that reduced connexin43 protein expression and/or changes in the phosphorylation status account for this astrocyte dysfunction. Remarkably, uncoupling occurred in the absence of neuronal death and reactive gliosis. These data provide a mechanistic link between FSs and the subsequent development of TLE and further strengthen the emerging view that astrocytes have a central role in the pathogenesis of this disorder. © 2016 Wiley Periodicals, Inc. Abstract : Hyperthermia‐induced experimental febrile seizures (FSs) cause a strong inhibition of gap junction‐mediated intercellular communication among hippocampal astrocytes, probably mediated by downregulation and/or changes in the phosphorylation status of connexin43. These data provide a mechanistic link between juvenile FSs and subsequent development of temporal lobe epilepsy.